IFNγ−IL-17+ CD8 T cells contribute to immunosuppression and tumor progression in human hepatocellular carcinoma. (1st January 2023) - Lee, Yun Hua; Chuah, Samuel; Nguyen, Phuong H.D.; Lim, Chun Jye; Lai, Hannah L.H.; Wasser, Martin; Chua, Camillus; Lim, Tony K.H.; Leow, Wei Qiang; Loh, Tracy Jiezhen; Wan, Wei Keat; Pang, Yin Huei; et al.
Abstract: IL-17-producing CD8 (Tc17) T cells have been shown to play an important role in infection and chronic inflammation, however their implications in hepatocellular carcinoma (HCC) remain elusive. In this study, we performed cytometry by time-of-flight (CyTOF) and revealed the distinctive immunological phenotypes of two IFNγ + and IFNγ − Tc17 subsets that were preferentially enriched in human HCC. Single-cell RNA-sequencing analysis further revealed regulatory circuits governing the different phenotypes of these Tc17 subsets. In particular, we discovered that IFNγ − Tc17 subset demonstrated pro-tumoral characteristics and expressed higher levels of CCL20. This corresponded to increased tumor infiltration of T regulatory cells (Treg) validated by immunohistochemistry in another independent HCC cohort, demonstrating the immunosuppressive functions of IFNγ − Tc17 subset. Most importantly, higher intra-tumoral proportions of IFNγ − Tc17 were associated with poorer prognosis in patients with HCC and this was further validated in The Cancer Genome Atlas (TCGA) HCC cohort. Taken together, this compendium of transcriptomic and proteomic data of Tc17 subsets sheds light on the immunosuppressive phenotypes of IFNγ − Tc17 and its implications in HCC progression. Highlights: Two distinct IFNγ + and IFNγ − Tc17 subsets were preferentially enriched in human HCC. Single-cell transcriptomic reveals the distinct regulatory circuits of Tc17 subsets. IFNγ − Tc17 expresses CCL20 that recruits immunosuppressive Treg cells. IFNγ − Tc17 is associated with poorer prognosis and survival of HCC patients.